Assessing the Impact of Reminiscence Therapy on Elderly Well-Being: A Pretest-Posttest Experimental Design - Nurhidayati, Euis; Novia Ramadina Pratiwi; Devi Rachmawati; Faizal Bahrain; Gabriel Steven Rikin; Karlina; Alifia Ulie Mizana Hadori (Universitas Muhammadiyah Metro, 2024)
The elderly are a group that faces complex challenges in this phase of their lives, including loneliness, social isolation, and decreased independence. This condition is often exacerbated by the loss of people close to them and a decline in physical health. Depression and anxiety often haunt older adults, which can go undiagnosed or ignored as part of the aging process. This study aims to evaluate the effect of providing reminiscence therapy on increasing the happiness of the elderly at the Adinda Mulia Bahagia Nursing Home. The method used is a one-group pretest-posttest design using a happiness scale-based questionnaire developed by Seligman (2002). The research was carried out at the Adinda Mulia Bahagia Foundation, Bekasi Regency, West Java on June 2 2024. The population consisted of all elderly people living in the institution, with samples taken using saturated sampling techniques. The results of data analysis using the t-test statistical test showed that there was a significant difference between the pretest and posttest scores (p < 0.05), indicating that reminiscence therapy had a positive effect on increasing the happiness of the elderly. Nevertheless, the correlation between pre- and post-treatment results shows inconsistent response variations among individuals. The conclusion of this research is that there is a significant change in the level of happiness of the elderly after being given reminiscence therapy, although individual responses may vary. As a suggestion, further research could expand the sample and consider additional factors that could influence the research results.